Method for predicting confinement mass transfer efficiency of two-dimensional separation membrane by adopting dielectric spectrum
The dielectric relaxation time in the two-dimensional separation membrane was measured by dielectric spectroscopy, and its limited-domain mass transfer efficiency was predicted, which solved the problems of inaccurate prediction and strong subjectivity in the prior art, and achieved a more accurate and efficient two-dimensional separation membrane research.
Patent Information
- Application Number
- CN202311075815.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-08-25
AI Technical Summary
In the prior art, the prediction of the limited-domain mass transfer efficiency of two-dimensional separation membranes is not accurate enough and is highly subjective, which leads researchers to waste time, energy and economic costs when screening conditions.
The method of predicting the domain mass transfer efficiency of two-dimensional separation membranes is adopted to predict the dielectric range of the two-dimensional separation membrane and the reference membrane by measuring the dielectric relaxation frequency of specific components in the two-dimensional separation membrane and the reference membrane, calculate the dielectric relaxation time, and judge the domain mass transfer efficiency based on the dielectric relaxation time ratio.
It realizes accurate and objective prediction of the limited-domain mass transfer efficiency of two-dimensional separation membranes, saves research time and cost, and provides technical support for the research on efficient separation of two-dimensional membranes.
Smart Images

Figure CN119499883A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane separation, and more specifically, relates to a method for predicting the confined mass transfer efficiency of a two-dimensional separation membrane by using dielectric spectroscopy. Background Art
[0002] As an energy-efficient and environmentally friendly technology, membrane separation technology has attracted increasing attention in the fields of gas purification, seawater desalination, biomass production and wastewater treatment. Separation technology using polymer, inorganic or composite membranes can achieve selective permeation of molecules based on molecular size differences or dissolution-diffusion processes. However, the design and separation efficiency of membranes are hindered by adhesion or the movement of polymer chains in porous structures and the trade-off effect between permeability and selectivity. Recent studies have shown that separation membranes based on two-dimensional materials maintain excellent selectivity while exhibiting high permeation rates, which is closely related to the abnormally high water transport properties and sub-nanometer channels with high flatness. A large number of literatures have reported that graphene oxide-based membranes have successfully achieved the effective separation of alcohol-water mixtures in biomass products by using the pervaporation process for efficient dehydration. In addition, researchers have used metal organic framework (MOF) nanosheet membranes with honeycomb structures and aluminum-free zeolite membranes based on stabilized zirconia for ethanol recovery. The researchers used spatial confinement to synthesize a (SiO2) / (silicalite-1) / (SiO2) sandwich membrane and used pervaporation to achieve n-butanol / water separation. In the prior art, researchers introduced cellulose nanofibers into covalent organic framework (COF) membranes to improve the stability of the membrane and achieve effective butanol dehydration. Therefore, the use of two-dimensional layered materials, based on the above advantages, is expected to break the trade-off restrictions in biomass dehydration applications and show great potential to become an efficient separation membrane.
[0003] It is reported in the prior art that some two-dimensional membranes can obtain better mass transfer efficiency after being modified (cross-linked) by cations or anions. However, the mass transfer efficiency of two-dimensional membrane separation is affected by many factors such as interlayer spacing, intercalation ion radius, valence state and temperature. Before actually separating the substances to be separated by two-dimensional membranes, it is impossible to accurately predict or characterize whether the mass transfer efficiency of the modified two-dimensional membrane is improved. This requires researchers to spend a lot of experiments to screen conditions before confirming whether the modified two-dimensional membrane has improved mass transfer efficiency, such as the type of modified ions of the modified membrane, the interaction between the permeating molecules and the channel, the interface interaction (conjugation and hydrophilicity), mass transfer structure, temperature, etc. When the optimal conditions are screened, once the mass transfer efficiency of the modified membrane is not substantially improved compared to the unmodified membrane, the aforementioned screening work will become invalid work, wasting the time, energy and economic cost invested by researchers in this subject.
[0004] In order to reduce the waste of time, energy and economic costs, researchers explored methods to predict the mass transfer efficiency of two-dimensional membrane separation. Unlike traditional polymer or nanoporous membranes, the size screening effect and richness of hydrophilic groups in two-dimensional membranes are not sufficient to achieve efficient separation of alcohol-water mixtures. Therefore, the separation mass transfer efficiency of two-dimensional membranes cannot be simply predicted by measuring thin film XRD or contact angle. However, subsequent studies have shown that the behavior and physical properties of confined water in two-dimensional membranes, such as strong hydrogen bond networks and possible monolayer water formation, will affect the rapid penetration of water and simultaneously block the penetration of alcohol, indicating that the separation mass transfer efficiency of two-dimensional membranes (especially alcohol-water separation) is related to the state of confined water in the two-dimensional membrane. However, confined water includes two parts: water in the capillary and water adsorbed on the surface. Only the state of water in the capillary is related to the mass transfer efficiency of two-dimensional membrane separation. Regarding the study of confined water and two-dimensional membrane separation mass transfer efficiency, the existing technology has only achieved the characterization of confined water from the perspective of the mass of confined water (capillary water and water adsorbed on the surface). For example, the adsorption curve of confined water is first measured using a quartz crystal microbalance (QCM), and then the mass of capillary water is determined by the different intervals of the slope of the adsorption curve, thereby establishing an indirect connection between the mass of capillary water and the permeation rate of the two-dimensional membrane. However, the judgment of the slope involved in this method is somewhat subjective, and it does not reflect the viscosity and other states of capillary water in the two-dimensional membrane. The mass transfer efficiency prediction results obtained in the end have certain limitations.
[0005] Therefore, there is an urgent need in this field for a technology that can effectively characterize the state of confined water in the membrane, which can accurately and objectively determine the mass transfer efficiency of the two-dimensional membrane for water and save research time and cost. Summary of the invention
[0006] 1. Problem to be solved
[0007] In view of the problems of inaccuracy and strong subjectivity in the prediction of confined mass transfer efficiency of two-dimensional separation membranes in the prior art, the present invention provides a method for predicting the confined mass transfer efficiency of two-dimensional separation membranes using dielectric spectroscopy. The method can accurately and objectively predict the confined mass transfer efficiency of the same or different types of two-dimensional separation membranes, effectively reflect the state and relative transfer rate of water between the two-dimensional separation membrane layers, and provide technical support for the research of efficient separation two-dimensional membranes.
[0008] 2. Technical solution
[0009] The technical solution adopted by the present invention is as follows:
[0010] The first aspect of the present invention provides a method for predicting the confined mass transfer efficiency of a two-dimensional separation membrane using dielectric spectroscopy.
[0011] The confined mass transfer efficiency includes the permeation rate;
[0012] Methods include:
[0013] S1 measures the dielectric spectra of specific components in the two-dimensional separation membrane and the reference membrane respectively, obtains the dielectric relaxation frequency, and then calculates the dielectric relaxation time; the dielectric relaxation frequency is obtained by fitting the dielectric spectrum curve with the Havriliak-Negami equation; the Havriliak-Negami equation is:
[0014]
[0015] Where ε' and ε" represent the real and imaginary parts of the dielectric constant, respectively; ε ∞ is the value of ε' at infinite high frequency, Δε represents the relaxation intensity, that is, ε' at zero frequency and infinite high frequency (ε ∞ ); τ is the characteristic dielectric relaxation time, ω represents the angular frequency; the parameters α and β are used to describe the skewness and broadening of the dielectric function, ranging from 0 to 1; j represents different Havriliak-Negami terms in multiple relaxation processes;
[0016] S2 determines the confined mass transfer efficiency of the specific component in the two-dimensional separation membrane according to the dielectric relaxation time ratio of the specific component in the two-dimensional separation membrane τ to the dielectric relaxation time τ0 of the reference membrane (this ratio can also be called relative relaxation time) τ / τ0:
[0017] When τ / τ0 is less than 1, it is judged that the confined mass transfer efficiency of the two-dimensional separation membrane for the specific component is higher than that of the reference membrane;
[0018] When τ / τ0 is greater than 1, it is judged that the confined mass transfer efficiency of the two-dimensional separation membrane for the specific component is lower than that of the reference membrane;
[0019] The two-dimensional separation membrane and the reference membrane are two-dimensional separation membranes that do not have conductivity.
[0020] According to the Debye model, the dielectric relaxation time τ in confined space can be expressed as:
[0021]
[0022] Where k and T are the Boltzmann constant and temperature respectively; a R represents the radius of the dipole molecular cluster; η is used to describe the viscosity of fluids (such as amino, organic solvents and ionic liquids). Therefore, τ represents the increased viscosity. In addition, the increased local viscosity generally leads to a slower penetration of molecules, which is consistent with the prediction of the Hagen-Poiseuille equation. Therefore, the viscosity of the confined fluid and its effect on molecular transport can be evaluated by studying the dielectric relaxation process.
[0023] Different from the relaxation process of bulk water in the range of 6-80 GHz, the relaxation process in the low frequency region (e.g.-3 ~10 3 The characteristic dielectric peak of 20 Hz can be used to characterize the confined water in 2D nanocapillaries without the need to remove the influence of the surface liquid as required by other techniques such as electrochemical quartz crystal microbalance (EQCM), infrared spectroscopy, neutron scattering, positron annihilation and nuclear magnetic resonance (NMR).
[0024] Theoretically, the method of the present invention is applicable to the prediction of the confined mass transfer efficiency of water or other non-aqueous solvents in two-dimensional separation membranes whose dielectric peaks can be observed on the dielectric spectrum. However, due to the limitation of the frequency range of the instrument, the present invention only carried out dielectric spectrum experimental prediction of the confined mass transfer efficiency of water in two-dimensional separation membranes, and verified the accuracy of the prediction through actual measurement. However, its principle is also applicable to the prediction of the confined mass transfer efficiency of other non-aqueous solvents in two-dimensional separation membranes whose dielectric peaks can be observed on the dielectric spectrum.
[0025] The second aspect of the present invention provides a method for predicting the confined mass transfer efficiency of a two-dimensional separation membrane using dielectric spectroscopy.
[0026] The confined mass transfer efficiency includes the permeation rate;
[0027] Methods include:
[0028] S1 was used to measure the water content of the two-dimensional separation membrane and the reference membrane at 10 -3 ~10 3 The dielectric spectrum in the Hz range is obtained, and after the dielectric relaxation frequency is obtained, the dielectric relaxation time is calculated; the dielectric relaxation frequency is obtained by fitting the dielectric spectrum curve with the Havriliak-Negami equation; the Havriliak-Negami equation is:
[0029]
[0030] Where ε' and ε" represent the real and imaginary parts of the dielectric constant, respectively; ε ∞ is the value of ε' at infinite high frequency, Δε represents the relaxation intensity, that is, ε' at zero frequency and infinite high frequency (ε ∞ ); τ is the characteristic dielectric relaxation time, ω represents the angular frequency; the parameters α and β are used to describe the skewness and broadening of the dielectric function, ranging from 0 to 1; j represents different Havriliak-Negami terms in multiple relaxation processes;
[0031] Water here refers to pure water or water in an aqueous system;
[0032] S2 determines the confined mass transfer efficiency of water in the two-dimensional separation membrane according to the dielectric relaxation time ratio of water in the two-dimensional separation membrane τ to the dielectric relaxation time τ0 of the reference membrane (this ratio can also be called relative relaxation time) τ / τ0:
[0033] When τ / τ0 is less than 1, it is judged that the confined mass transfer efficiency of the two-dimensional separation membrane for water is higher than that of the reference membrane;
[0034] When τ / τ0 is greater than 1, it is judged that the confined mass transfer efficiency of the two-dimensional separation membrane for water is lower than that of the reference membrane;
[0035] The two-dimensional separation membrane and the reference membrane are two-dimensional separation membranes that do not have conductivity.
[0036] The permeation rate in the present invention refers to the ability of the membrane to allow fluid to pass through a unit area of the membrane per unit time without destroying its medium structure.
[0037] In the present invention, dielectric relaxation is measured by a dielectric spectrometer, and dielectric relaxation represents the process in which microscopic particles in the system are polarized by an external electric field to produce polarization intensity (i.e., non-thermal equilibrium state), and return to a thermal equilibrium state after removing the external electric field. The greater the degree of confinement of water between the two-dimensional material layers, the greater the viscosity of the confined water and the longer the dielectric relaxation time. Under the same conditions, the shorter the dielectric relaxation time of water in the two-dimensional separation membrane, the smaller the viscosity of the confined water and the smaller the degree of confinement of the water, and therefore the faster the water permeation rate. On the contrary, the longer the dielectric relaxation time of water in the two-dimensional separation membrane, the greater the viscosity of the confined water and the greater the degree of confinement of the water, and therefore the slower the water permeation rate.
[0038] The Eyring model (Equation 3) can be used to understand the thermodynamic properties of water confined in two-dimensional interlayers:
[0039]
[0040] Among them, h and k B represents Planck's constant and Boltzmann's constant respectively; ΔS and ΔH represent the entropy change and enthalpy change during the polarization process respectively. In a confined space, a higher ΔH means that more hydrogen bonds need to be broken during the relaxation process to form larger molecular clusters, while a smaller ΔS indicates that the molecular clusters become more ordered under the action of an external field.
[0041] As a preferred embodiment of the technical solution of the second aspect of the present invention, when τ / τ0 is equal to 1, it is judged that the confined mass transfer efficiency of the two-dimensional separation membrane for water is basically the same as that of the reference membrane.
[0042] As a preferred embodiment of any technical solution of the second aspect of the present invention, the two-dimensional separation membrane includes a two-dimensional membrane of the same type or a different type as the reference membrane. For example, the two-dimensional separation membrane is a vermiculite two-dimensional membrane, and the reference membrane is a graphene oxide two-dimensional membrane, or the two-dimensional separation membrane is a graphene oxide two-dimensional membrane, and the reference membrane is a vermiculite two-dimensional membrane.
[0043] As a preferred embodiment of any technical solution of the second aspect of the present invention, the two-dimensional separation membrane includes a membrane obtained by cation modification or anion modification based on a reference membrane. This is a two-dimensional membrane of the same type. For example, for materials with negative charges on the surface, cation modification can be used, and the modified cations can be metal ions, ammonium ions, quaternary ammonium salts, etc.; for materials with positive charges on the surface, anion modification can be used, and the modified anions can be oxalic acid, carbonic acid, etc.
[0044] As a preferred embodiment of any technical solution of the second aspect of the present invention, the reference membrane or the two-dimensional separation membrane is independently selected from a graphene oxide two-dimensional membrane or a cation-modified graphene oxide two-dimensional membrane.
[0045] As a preferred embodiment of any technical solution of the second aspect of the present invention, the reference membrane is a graphene oxide two-dimensional membrane, and the two-dimensional separation membrane is a cation-modified graphene oxide two-dimensional membrane; the surface of the graphene oxide two-dimensional membrane is negatively charged and is generally modified by cations.
[0046] As a preferred embodiment of any technical solution of the second aspect of the present invention, the reference membrane is a mica two-dimensional membrane, and the two-dimensional separation membrane is a cation-modified mica two-dimensional membrane; or the reference membrane is a cation-modified mica two-dimensional membrane, and the two-dimensional separation membrane is a mica two-dimensional membrane; the surface of the mica two-dimensional membrane is negatively charged and is generally modified by cations.
[0047] As a preferred embodiment of any technical solution of the second aspect of the present invention, the reference membrane is a COF two-dimensional membrane, and the two-dimensional separation membrane is a cation-modified COF two-dimensional membrane or an anion-modified COF two-dimensional membrane; or the reference membrane is a cation-modified COF two-dimensional membrane or an anion-modified COF two-dimensional membrane, and the two-dimensional separation membrane is a COF two-dimensional membrane; the surface charge of the COF two-dimensional membrane is determined by the functional groups. When the surface functional groups have negative charges, cation modification is generally used; when the surface functional groups have positive charges, anion modification is generally used.
[0048] As a preferred embodiment of any technical solution of the second aspect of the present invention, the reference membrane is a MOF two-dimensional membrane, and the two-dimensional separation membrane is a cation-modified MOF two-dimensional membrane or anion-modified MOF two-dimensional membrane; or the reference membrane is a cation-modified MOF two-dimensional membrane or anion-modified MOF two-dimensional membrane, and the two-dimensional separation membrane is a MOF two-dimensional membrane. The surface charge of the MOF two-dimensional membrane is determined by the functional group. When the surface functional group has a negative charge, cation modification is generally used; when the surface functional group has a positive charge, anion modification is generally used.
[0049] As a preferred embodiment of any technical solution of the second aspect of the present invention, when the reference membrane is a graphene oxide two-dimensional membrane and the two-dimensional separation membrane is a cation-modified graphene oxide two-dimensional membrane, the cation-modified graphene oxide two-dimensional membrane includes Al 3+Modified graphene oxide two-dimensional film, Mn 2+ Modified graphene oxide two-dimensional film, La 3+ Modified graphene oxide two-dimensional film or Ba 2+ One or more of modified graphene oxide two-dimensional films.
[0050] As a preferred embodiment of any technical solution of the second aspect of the present invention, the reference membrane or the two-dimensional separation membrane is independently selected from a graphene oxide two-dimensional membrane and a vermiculite two-dimensional membrane. For example, the reference membrane can be a graphene oxide two-dimensional membrane, and the two-dimensional separation membrane can be a vermiculite two-dimensional membrane, or vice versa.
[0051] As a preferred embodiment of any technical solution of the second aspect of the present invention, the water is pure water or water in an aqueous system. When it is pure water, the confined mass transfer efficiency is mainly manifested as the permeation rate of water in the two-dimensional membrane. When it is water in an aqueous system, it means that the system also contains other solvents besides water. The confined mass transfer efficiency is mainly manifested as the permeation rate of water in the two-dimensional membrane and the selectivity of the two-dimensional membrane for water. For example, the selectivity is obtained in the embodiment of the present invention by first measuring the permeation rate of the substance in a unit system, i.e., 100% water or 100% alcohol, respectively; and then the ratio of the water permeation rate to the alcohol permeation rate is regarded as the selectivity. The selectivity can also be obtained by directly using a mixed system of water and alcohol to test the dielectric spectrum.
[0052] As a preferred embodiment of any technical solution of the second aspect of the present invention, the water-containing system is an alcohol-water system. The alcohol-water system refers to a system in which any alcohol and water are miscible in any proportion, such as ethanol / water, propanol / water, isopropanol / water, isobutanol / water, and n-butanol / water, where the water is present in a proportion of 0.1 to 99.9%. For example, the proportion of water is 10%, 20%, 30%, 50%, 80%, etc.
[0053] As a preferred embodiment of any technical solution of the second aspect of the present invention, the applicable temperature is 0 to 35°C.
[0054] 3. Beneficial effects
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] (1) The present invention is the first to discover the correlation between the state of water between the two-dimensional separation membrane layers and the relative transmission rate (permeation rate) and dielectric relaxation; the method of the present invention measures dielectric relaxation through dielectric spectroscopy, and accurately predicts whether the same type of two-dimensional separation membrane, such as a modified two-dimensional separation membrane, has improved confined mass transfer efficiency for water relative to an unmodified two-dimensional separation membrane through the change in dielectric relaxation (relative dielectric relaxation time), and vermiculite two-dimensional separation membranes of different types have been verified, such as graphene oxide two-dimensional membranes and vermiculite two-dimensional membranes. This provides technical support for the research on high-efficiency two-dimensional separation membranes; compared with traditional methods for characterizing two-dimensional membranes to predict mass transfer efficiency, such as contact angle and XRD, the dielectric spectroscopy method of the present invention is more concise, efficient, accurate and objective in reflecting the mass transfer efficiency of water in two-dimensional separation membranes.
[0057] (2) The present invention uses graphene oxide two-dimensional membrane, vermiculite two-dimensional membrane, etc. as examples, and adopts dielectric spectroscopy method to predict the confined mass transfer efficiency of water in the two-dimensional membrane, and conducts experimental verification. The verification results show that the dielectric spectroscopy prediction is consistent with the experimental results. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 : (a, b) Top view and side view SEM images of free-standing graphene oxide two-dimensional film (GO); (c, d) top view and side view SEM images of vermiculite two-dimensional film.
[0059] Figure 2 : (a, c) Tapping mode AFM images of GO and vermiculite nanosheets deposited on Si wafer substrate; (b, d) corresponding GO and vermiculite nanosheet height profiles.
[0060] Figure 3 :(a) XPS spectra of GO 2D film, (b) GO-Al film, (d) GO-Mn film, (f) GO-La film, (h) GO-Ba film. (c) XPS Al 2p peak of GO-Al film; (e) XPS Mn 2p peak of GO-Mn film; (g) XPS La3d peak of GO-La film; (i) XPS Ba 3d peak of GO-Ba film.
[0061] Figure 4 : (a) Schematic diagram of the top view of the dielectric testing device; (b) Schematic diagram of the side view of the dielectric testing device.
[0062] Figure 5 :Dielectric study of graphene oxide (GO) two-dimensional film:
[0063] (a) Schematic diagram of dielectric spectrum measurement of the gold electrode / two-dimensional film / gold electrode sandwich structure device.
[0064] (b) The imaginary part of the dielectric constant ε" of GO 2D film at 25 °C with different humidity. The curve is fitted by the Havriliak-Negami equation (Equation 2), and the peak filled with shadows is attributed to confined water.
[0065] (c) The imaginary part of the dielectric constant ε" of the dielectric loss of GO 2D film in ethanol environment at 25 °C.
[0066] (d) Changes in relaxation time τ (left y-axis: red dot graph) and water content (right y-axis: blue bar graph) of GO 2D membranes at different relative humidity (RH) at 25 °C, ranging from 40% to 90%.
[0067] Figure 6 : (a) Variation of the imaginary part of the dielectric constant ε" of the dielectric loss of GO two-dimensional film at different temperatures under 90% relative humidity. The curve is fitted by the Havriliak-Negami formula, and the peak filled by the shadow is attributed to the confined water molecules.
[0068] (b) The dependence of the dielectric relaxation time τ (obtained experimentally) of the original GO film on temperature in the temperature range (10°C to 30°C) fitted by the Eyring model. The red line is the fitting line of the Eyring model.
[0069] Figure 7 :Study on dielectric relaxation and mass transfer behavior of ion-crosslinked (modified) graphene oxide two-dimensional membrane. (a) Al 3+ Variation of the imaginary part of the dielectric constant ε" of the cross-linked GO two-dimensional film with frequency.
[0070] (b) La at 25℃ and different humidity 3+ Variation of the imaginary part of the dielectric constant ε" of the cross-linked GO two-dimensional film with frequency.
[0071] (c) At 25℃ and different humidity, the 2+ Variation of the imaginary part of the dielectric constant ε" of the cross-linked GO two-dimensional film with frequency.
[0072] (d) Ba at 25℃ and different humidity 2+ Variation of the imaginary part of the dielectric constant ε" of the cross-linked GO two-dimensional film with frequency.
[0073] The curves are fitted by the Havriliak-Negami formula and the peaks filled by shadows are attributed to confined water.
[0074] Figure 8 :(a)Al 3+ , Mn 2+ ,La 3+ , Ba 2+Variation of the imaginary part of the dielectric constant ε" of the cross-linked GO two-dimensional film with frequency at 90% RH and 25°C. The above ion-modified cross-linked two-dimensional films (GO-X) are named GO-Al / Mn / La / Ba, respectively. (b) Ratio of the relaxation time of GO-Al and GO-La films to the dielectric relaxation time of GO two-dimensional film at different relative humidities.
[0075] (c) Relationship between water permeation (left y-axis) and the permeation rate ratio of water to isopropanol (right y-axis) of ion-crosslinked 2D membranes at 90% RH and 25°C and the corresponding relaxation time τ (upper x-axis). The red curve is a visual aid. Left y-axis: dot plot; right y-axis: blue bar graph.
[0076] Fig. 9 :Contact angle characterization method for predicting water permeation rate in two-dimensional membranes: (a) Contact angle photos of GO two-dimensional membranes with different ion crosslinking. (b) Contact angle trend (left y-axis) and pure water permeation rate (right y-axis) of GO two-dimensional membranes with different ion crosslinking. Fig.10 : XRD characterization for predicting water permeation rate in two-dimensional membranes (a) XRD patterns of GO two-dimensional membranes with different ion crosslinking at 25 °C and 100% RH. (b) Interlayer spacing trend (left y-axis) and experimentally verified pure water permeation rate (right y-axis) of GO two-dimensional membranes with different ion crosslinking.
[0077] Fig.11 : (a) Imaginary part of the dielectric constant ε" of GO two-dimensional membrane (GO) and vermiculite two-dimensional membrane (V) at 90% RH and 25°C. The curves were fitted using the Havriliak-Negami formula, and the peaks filled with shaded areas represent confined water. (b) Bar graph of water and isopropanol permeation rates of GO two-dimensional membrane and vermiculite two-dimensional membrane (left y-axis) and the ratio of water to isopropanol permeation rates (★, right y-axis). DETAILED DESCRIPTION
[0078] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs; the term "and / or" used herein includes any and all combinations of one or more of the associated listed items.
[0079] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0080] Concentration, amount and other numerical data can be presented in range format herein.It should be understood that such range format is only used for convenience and simplicity, and should be flexibly interpreted as not only including the numerical value clearly described as range limit, but also including all single numerical values or sub-ranges contained in the range, just as each numerical value and sub-range are clearly described.For example, the numerical range of about 1 to about 4.5 should be interpreted as not only including the limit value of 1 to about 4.5 clearly described, but also including single numerals (such as 2,3,4) and sub-ranges (such as 1 to 3,2 to 4, etc.).The same principle is applicable to the scope of only narrating a numerical value, such as "less than about 4.5", which should be interpreted as including all the above-mentioned values and ranges.In addition, no matter how the breadth of the described range or feature is, this explanation should be applicable.
[0081] Experimental Section
[0082] Materials: Expanded vermiculite was purchased from Shijiazhuang Chenxing Industrial Co., Ltd. Freeze-dried graphene oxide (GO) nanosheets with a size greater than 500 nm were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. (XFNANO). Chemical reagents such as sodium chloride (NaCl), lithium chloride (LiCl), aluminum chloride hexahydrate (AlCl3·6H2O), manganese chloride tetrahydrate (MnCl2·4H2O), lanthanum chloride (LaCl3) and barium chloride dihydrate (BaCl2·2H2O) were purchased from Tianjin Xiensiopude Technology Co., Ltd. Examples Deionized water purified by a (18.2 MΩ) Millipore Milli-Q system was used in all syntheses and analyses.
[0083] The present invention is further described below in conjunction with specific embodiments.
[0084] 1. Graphene oxide film (GO film or GO two-dimensional film), Al 3+ Modified graphene oxide two-dimensional film (GO-Al film), Mn 2+ Modified graphene oxide two-dimensional film (GO-Mn film), La 3+ Modified graphene oxide two-dimensional film (GO-La film) or Ba 2+ Preparation of modified graphene oxide two-dimensional film (GO-Ba film)
[0085] Freeze-dried graphene oxide (GO) nanosheets were dispersed in ultrapure water and stirred overnight, followed by 15 min of ultrasonic treatment. Subsequently, the GO nanosheet dispersion was centrifuged at a low speed to remove the undispersed multilayer GO nanosheets (3000 rpm / min, retaining the supernatant). It was then centrifuged at a high speed to remove nanosheets with smaller sheet sizes (8000 rpm / min, retaining the bottom colloid). After high-speed centrifugation, the colloid was dispersed in ultrapure water to obtain a single-layer GO nanosheet colloidal solution.
[0086] By vacuum filtration, the single-layer GO nanosheets were assembled into a two-dimensional nanosheet film (GO membrane).
[0087] At room temperature, the GO membranes were immersed in 1M AlCl3, MnCl2, LaCl3 and BaCl2 solutions, respectively, and ion crosslinked for 12 hours to prepare GO-Al membrane, GO-Mn membrane, GO-La membrane and GO-Ba membrane, respectively. After the crosslinking, the membranes were rinsed with deionized water to remove residual ions on the membrane surface, and finally dried naturally to obtain GO-Al membrane, GO-Mn membrane, GO-La membrane and GO-Ba membrane.
[0088] 2. Preparation of Vermiculite Membrane (Vermiculite Two-Dimensional Membrane)
[0089] Vermiculite was exfoliated into nanosheets by ion intercalation. First, 0.20 g of vermiculite was mixed with 200 mL of saturated NaCl solution and refluxed at 120 °C for 24 h to obtain intercalated Na + After the reaction, the product was filtered through a polyethersulfone (PES) membrane and washed with a large amount of deionized water to remove excess salt. + The exchanged vermiculite was mixed with 200 mL of 2M LiCl solution and refluxed at 120 °C with magnetic stirring for 24 h. The product was filtered through the same washing process as before to obtain Li + After the ion intercalation is completed, Li + The exchanged vermiculite was dispersed in ultrapure water and subjected to ultrasonic treatment for 30 min to exfoliate it into single-layer nanosheets. The obtained colloidal solution was then centrifuged multiple times at 3000 rpm / min to remove the unexfoliated vermiculite, and then centrifuged at 10000 rpm / min to remove the smaller nanosheets. Finally, the nanosheets were reassembled into a self-supporting membrane (vermiculite membrane or vermiculite two-dimensional membrane) by vacuum filtration.
[0090] 3. Characterization
[0091] The surface morphology of the 2D nanosheets and membranes, as well as the thickness of the membranes (GO membrane and vermiculite membrane) were obtained by observation on a Carl Zeiss Merlin high-resolution field emission scanning electron microscope (FE-SEM) operating at a voltage of 5.0 kV ( Figure 1 ).
[0092] X-ray diffraction (XRD) data were acquired using a Rigaku benchtop X-ray diffractometer equipped with a HyPix-400MF 2D hybrid pixel array detector (HPAD) and Cu Kα radiation (λ = 0.15405 nm), operating at 40 kV and 15 mA in Bragg-Brentano mode. The interlayer distance of the membrane was tested at different humidities: Saturated salt solutions were prepared by dissolving different amounts of salt in deionized water to obtain different relative humidity (RH): LiCl (12% RH), MgCl2 (33% RH), NaCl (75% RH) and KCl (84% RH). The membrane was placed above an XRD test device containing different saturated salt solutions. Prior to the measurement, the device was placed in a sealed container containing the same saturated salt solution for 4 h.
[0093] The thickness of the nanosheets was measured using an atomic force microscope (AFM) using Dimension ICON-PT (Bruker) in vibration mode. Figure 2 ).
[0094] X-ray photoelectron spectroscopy (XPS, Thermo Kalpha) was used to study the chemical composition of GO and GO membranes with different ion crosslinking (cation-modified GO membranes). Figure 3 ).
[0095] 4. Preparation of Dielectric Test Device
[0096] In order to manufacture a flexible dielectric test device (see the schematic diagram of the specific device for details), Figure 4 ), use epoxy resin to encapsulate the two-dimensional film and two pieces of PET with holes to form a sandwich structure of PET / GO / PET. Before spraying gold, use masking tape to cover the edges of the PET to avoid covering areas that do not need to be covered with gold. Then, use an ion sputtering instrument to spray gold on the front and back of the device separately at a current of 10mA (90s) to prepare metal electrodes. The copper foil with copper wire welded on it is pasted on the edges of the PET holes and the two-dimensional film with carbon tape, and silver glue is applied to the connection between the two to enhance conductivity. The other end of the copper wire is welded to a copper sheet, which is connected to a fixture for dielectric spectrum testing.
[0097] 5. Dielectric relaxation spectrum test
[0098] All dielectric spectroscopy measurements in this invention were obtained using an MFIA impedance analyzer in Zurich, controlled by LabOne software. When an alternating electric field is applied to a two-dimensional film sample, water molecules are polarized and cause dipole rotation, and information about the impedance (Z*=Z'+jZ") with respect to frequency can be collected, where Z' and Z" are the real and imaginary parts of the impedance obtained from the electrochemical impedance spectroscopy (EIS), respectively. This information is then converted into the frequency dependence of the complex dielectric constant (ε*) using equations (1), (2), and (3).
[0099]
[0100]
[0101]
[0102] Where ε' (dielectric constant) and ε" (dielectric loss factor) are the real and imaginary parts of the dielectric constant, respectively; ω is the angular frequency (ω = 2πf), f is the frequency, C0 (ε0A / d) is the capacitance of the film, and ε0 is the vacuum dielectric constant (8.854×10 -14 F cm –1 ).
[0103] 6. Membrane water content test
[0104] Before the measurement, the membrane sample was placed in a glove box overnight to remove the water absorbed by the membrane outdoors, and then the weight of the membrane (m 0% RH ), and then remove the membrane from the glove box for testing. Place the dried membrane on a balance in a constant temperature and humidity test chamber, with the initial setting conditions being 25°C, 30% RH. At this point, the software Launch SPDC Data Collection V 2.03 that comes with the quasi-microbalance is enabled to record the real-time weight of the membrane. Maintain this condition for 4 hours to ensure the stability of the membrane state. When the membrane weight hardly changes over time, record the weight of the membrane at this time as (m 30% RH ). Under this condition, the humidity in the constant temperature and humidity test chamber is then increased by 10% RH while maintaining the temperature unchanged. The same humidity is maintained for 4 hours. At x% RH, the water content formula is:
[0105] (m x%RH -m 0% RH ) / m 0% RH ×100% Formula 4.
[0106] 7. Water / isopropyl alcohol system permeability test
[0107] The sample membrane is encapsulated in a test device filled with alcohol or water. In order to measure the permeation rate of the membrane to water, the above device is placed in a test box with a quasi-microbalance, and the test conditions of the test box are 25°C and 30% relative humidity. However, for the permeation rate test of alcohol, since the membrane may absorb water from the air, it is necessary to place the above permeation test device in a quasi-microbalance in a glove box. The weight change of the permeation device over time, i.e., the weight loss curve, is recorded using the software provided by the quasi-microbalance.
[0108] 8. Dielectric relaxation of GO membrane at different relative air humidity and temperature
[0109] (1) Dielectric relaxation of two-dimensional membranes (taking GO membrane as an example) at different relative humidity
[0110] First, the schematic diagram of the dielectric test setup is shown in Figure 4 According to the method of the fourth part, a double-sided gold-sprayed GO film (the GO film is the GO film prepared in the first part) is prepared to perform dielectric spectrum testing ( Figure 5 a). To obtain τ, the complex dielectric constant ε(ω) can be described using the semi-empirical expression Havriliak-Negami equation proposed by Havriliak and Negami, which contains multiple dipole dynamic parameters:
[0111]
[0112] Where ε' and ε" represent the real and imaginary parts of the dielectric constant, respectively; ε ∞ is the value of ε' at infinite high frequency, Δε represents the relaxation intensity, that is, ε' at zero frequency and infinite high frequency (ε ∞ ); τ is the characteristic dielectric relaxation time, ω represents the angular frequency; the parameters α and β are used to describe the skewness and broadening of the dielectric function, and their values range from 0 to 1; j represents different Havriliak-Negami terms in multiple relaxation processes.
[0113] Based on formula 2, for the GO membrane placed in different relative humidity environments (30% RH, 50% RH, 70% RH, 90% RH) at 25°C, the dielectric spectrum of the imaginary part of the dielectric constant ε" is fitted, as shown in Figure 5 As shown in b, the Havriliak-Negami peak was observed to appear at 10 -3 Up to 10 3 Hz range. In contrast, when the GO film was exposed to anhydrous ethanol vapor, the dielectric peak disappeared ( Figure 5 c) The above results show that from 10 -3 Up to 10 3The dielectric relaxation process in the Hz range is attributed to the confined water in the two-dimensional membrane (2D nanocapillary).
[0114] The dielectric relaxation time of the GO membrane was studied by dielectric spectra at different relative humidity (RH) at 25°C. As the humidity increased linearly from 40% to 90% RH, the dielectric relaxation time decreased exponentially ( Figure 5 d), at this time the water content in the membrane increased from 10.3% to 63.9%.
[0115] (2) Dielectric relaxation of two-dimensional membranes (taking GO membrane as an example) at different temperatures
[0116] In addition, we also tested the dielectric relaxation of GO films at different temperatures (10 to 35°C) ( Figure 6 ), the results show that, when other conditions are the same, the higher the temperature, the shorter the dielectric relaxation time of water in the GO membrane. This is because the higher the temperature, the more intense the molecular thermal motion and the enhanced molecular dipole rotation.
[0117] IX. Relationship between dielectric relaxation and water permeability of cation-crosslinked GO membranes
[0118] According to the above research results, dielectric spectroscopy can reveal the internal molecular state of the material transport in the modified GO membrane. As a common modification method, ionic crosslinking can improve the selectivity and stability of the membrane and has been widely used in gas separation, seawater desalination and nanofiltration. However, in addition to the regulation of channel size, the effect of charged ions on confined water has rarely been reported. In this section, we used different cations (Al 3+ , Mn 2+ ,La 3+ , Ba 2+ ) cross-linked GO two-dimensional membrane (preparation method see the first part) as an example to demonstrate the applicability of dielectric spectroscopy in predicting water permeation rate in two-dimensional separation membranes.
[0119] Figure 7 Shows Al 3+ , Ba 2+ ,La 3+ , Mn 2+ The imaginary part of the dielectric constant ε" of the cross-linked GO membrane at 25℃ and different humidity (30%RH, 50%RH, 70%RH, 90%RH) varies with frequency. It can be seen from the figure that the dielectric relaxation peaks of the four cationic cross-linked membranes are all at 10 -3 Hz to 10 3 Hz range. With the increase of humidity, the dielectric relaxation peaks of the four cation-crosslinked membranes shifted to higher frequencies, which is different from the original GO membrane ( Figure 5However, at the same humidity (90%) and temperature (25 °C), there are significant differences in the dielectric relaxation peak frequencies of GO membranes cross-linked with different cations (Table 1).
[0120] Table 1 Relative dielectric relaxation time τ / τ0 of confined water in cation-modified graphene oxide membrane at RH90%
[0121] GO membrane GO-Al membrane GO-Mn membrane GO-La film GO-Ba film Dielectric relaxation frequency (Hz) 54.50 128.00 14.90 10.28 0.48 Dielectric relaxation time τ(s) <![CDATA[0.0029(τ0)]]> 0.00124 0.01068 0.01548 0.3316 <![CDATA[Relative dielectric relaxation time τ / τ0]]> 1 0.4287 3.6832 5.3386 114.3354
[0122] For example, Figure 7 a, The dielectric relaxation peak of the GO-Al film at 90% RH is located at 128 Hz, which is higher than the dielectric relaxation frequency of the original GO film (54.5 Hz). Figure 6 (a)). As a comparison, another trivalent cation La 3+ The dielectric relaxation peak of the cross-linked GO film is located at a lower frequency than that of the original GO film. The dielectric relaxation time of the original GO film at different humidity is τ0, and the relaxation time τ0 of the GO-La and GO-Al films relative to the original GO film shows an opposite trend at all humidity ( Figure 7 a and 7b). The relative relaxation time of the GO-Al membrane (i.e., the dielectric relaxation time ratio of the two-dimensional separation membrane dielectric relaxation time τ to the reference membrane dielectric relaxation time τ0) τ / τ0 is less than 1, indicating that the state of the confined water is more “relaxed” relative to the original GO membrane, while the slower relaxation process of the GO-La membrane (τ / τ0 is greater than 1) indicates that the confined water molecules are more “confined”. Figure 7 c and 7d are respectively in the presence of divalent cation Ba 2+ and Mn 2+ Frequency dependence of the imaginary part of the dielectric relaxation peak of the cross-linked GO film at different humidity levels. Figure 8 a It can be seen that the dielectric relaxation processes of the two (GO-Ba and GO-Mn) at 90% RH are extremely different. The dielectric peak frequency of the GO-Mn membrane (14.9 Hz) is much higher than that of the GO-Ba membrane (0.48 Hz), which indicates that at 90% RH, the water in the GO-Ba membrane is more restricted and has a greater viscosity. Therefore, we speculate that the GO-Mn membrane has a higher permeability rate to water than the GO-Ba membrane.
[0123] According to the above relative dielectric relaxation time τ / τ0, the permeation rate of confined water in the cation-modified graphene oxide membrane is predicted to be in the order of GO-Al>GO-Mn>GO-La>GO-Ba.
[0124] 10. Measured water permeability of cationic cross-linked GO membrane
[0125] According to the water permeability of the GO membranes with cation cross-linking measured in water / isopropanol in the seventh part and the original GO membranes (prepared in the first part), the test conditions are as follows: the temperature is 25 °C, and the relative humidity is 30%. The water permeation rates measured in the experiment show the following trend: GO-Al > GO-Mn > GO-La > GO-Ba( Figure 8 c).
[0126] The selectivity is obtained as follows: First, measure the permeation rates of substances in the unit systems of 100% water or 100% isopropanol respectively; then regard the ratio of the water permeation rate to the isopropanol permeation rate as the selectivity. The results show that the relationship between the ratio of the isopropanol and water permeation rates and the corresponding relative relaxation time τ / τ0 also conforms to the predicted trend.
[0127] XI. Prediction of the water permeability of cation-crosslinked GO membranes using contact angle and XRD
[0128] In the prior art, other characterization methods are used to explain the selective transport of 2D layered materials, such as contact angle measurement and XRD characterization. To compare the prediction accuracy, we also used other characterization methods to explore the water mass transfer efficiency of cation-crosslinked GO membranes( Fig. 9 and Fig.10 ).
[0129] (1) Contact angle
[0130] Contact angle measurement is a commonly used method for characterizing surface properties and can be used to evaluate the wettability on the membrane surface, thereby predicting the interaction between water and the interlayer transport channels. As Fig. 9 a, in the cation-crosslinked GO membranes, the increasing order of the contact angle is: GO-Al < GO-Mn < GO-Ba < GO-La, indicating that compared with the original GO membrane (contact angle of 43°), the interlayer hydrophilicity weakens. According to previous studies, enhanced surface hydrophilicity will lead to an increase in water permeation. However, the predicted water permeation by contact angle measurement does not match the experimental results( Fig. 9 b).
[0131] As a surface chemical characterization method, the test results of contact angle measurement are usually affected by surface roughness in addition to the inherent properties of substances. Different preparation methods, such as vacuum-assisted filtration, gas-liquid self-assembly, spin coating or blade coating, will result in membranes with different surface properties (such as surface energy, roughness, surface charge), thus causing misunderstandings about the interlayer transport.
[0132] (2) XRD
[0133] In-situ XRD is also a method used in the prior art to evaluate the channel size effect. Therefore, the present invention measures the XRD spectrum of the cationic cross-linked GO membrane at 100% relative humidity and discusses the effect of the interlayer channel size on the interlayer mass transfer ( Fig.10 ). The results show that the changes in the interlayer space are inconsistent with the changes in water penetration.
[0134] In contrast, the state of confined water within 2D nanocapillaries was directly monitored by the dielectric relaxation method, providing a reliable approach to promote the rational design of separation membranes based on 2D materials.
[0135] 12. Prediction of water permeability of vermiculite two-dimensional membranes using dielectric relaxation method
[0136] This dielectric study is also applicable to the evaluation of other 2D material-based membranes. For example, the dielectric relaxation peak of water in the vermiculite membrane (prepared according to the second part of the method) is located at a lower frequency position (τ / τ0>1) than that in the GO membrane (prepared according to the first part of the method), indicating a slower dielectric relaxation process ( Fig.11 a), resulting in a decrease in water permeation rate and separation factor (selectivity) (experimental verification such as Fig.11 b).
[0137] In the present invention, the dielectric properties of the alcohol-water separation membrane based on graphene oxide (GO) are explored. By analyzing the dielectric relaxation process, the additional viscosity caused by confinement in the low-frequency region of the dielectric spectrum can be evaluated. The results show that cationic intercalation (cross-linking) can regulate the viscosity of confined water to achieve the purpose of increasing or reducing the permeation rate of water, thereby adjusting the selectivity of alcohol-water separation. Compared with the evaluation method of XRD or contact angle measurement, the dielectric study of the present invention more accurately and comprehensively reflects the mass transfer efficiency of water transmission in the two-dimensional membrane. Therefore, the dielectric spectrum can promote the development of efficient two-dimensional separation membrane materials by deeply insight into the nanofluidics of 2D nanochannels.
[0138] The above content is a schematic description of the present invention and its implementation methods, which is not restrictive. What is shown in the embodiment is only one of the implementation methods of the present invention, and the actual implementation method is not limited thereto. Therefore, if a person of ordinary skill in the art is inspired by it and designs implementation methods and embodiments similar to the technical solution without creative design without departing from the purpose of the invention, they should all fall within the scope of protection of the present invention.
Claims
1. A method for predicting the confined mass transfer efficiency of a two-dimensional separation membrane using dielectric spectroscopy, characterized in that: The confined mass transfer efficiency includes the permeation rate; Methods include: S1 was used to measure the water content of the two-dimensional separation membrane and the reference membrane at 10 -3 ~10 3 The dielectric spectrum in the Hz range is obtained, and after the dielectric relaxation frequency is obtained, the dielectric relaxation time is calculated; the dielectric relaxation frequency is obtained by fitting the dielectric spectrum curve with the Havriliak-Negami equation; the Havriliak-Negami equation is: Where ε' and ε" represent the real and imaginary parts of the dielectric constant, respectively; ε ∞ is the value of ε' at infinite frequency, Δε represents the relaxation intensity, that is, ε' at zero frequency and infinite frequency ε ∞ The difference between them; τ is the characteristic dielectric relaxation time, ω represents the angular frequency; the parameters α and β are used to describe the skewness and broadening of the dielectric function, ranging from 0 to 1; j represents different Havriliak-Negami terms in multiple relaxation processes; S2 determines the confined mass transfer efficiency of water in the two-dimensional separation membrane based on the dielectric relaxation time ratio τ / τ0 of the dielectric relaxation time τ of the water in the two-dimensional separation membrane and the dielectric relaxation time τ0 of the reference membrane: When τ / τ0 is less than 1, it is judged that the confined mass transfer efficiency of the two-dimensional separation membrane for water is higher than that of the reference membrane; When τ / τ0 is greater than 1, it is judged that the confined mass transfer efficiency of the two-dimensional separation membrane for water is lower than that of the reference membrane; The two-dimensional separation membrane and the reference membrane are two-dimensional separation membranes that do not have conductivity.
2. The method for predicting the confined mass transfer efficiency of a two-dimensional separation membrane using dielectric spectroscopy according to claim 1, characterized in that: The two-dimensional separation membrane includes a two-dimensional membrane of the same type or a different type as the reference membrane.
3. The method for predicting the confined mass transfer efficiency of a two-dimensional separation membrane using dielectric spectroscopy according to claim 1, characterized in that: The two-dimensional separation membrane includes a membrane obtained by modifying a reference membrane with cations or anions.
4. The method for predicting the confined mass transfer efficiency of a two-dimensional separation membrane using dielectric spectroscopy according to claim 1, characterized in that: The reference membrane or the two-dimensional separation membrane is independently selected from a graphene oxide two-dimensional membrane or a cation-modified graphene oxide two-dimensional membrane.
5. The method for predicting the confined mass transfer efficiency of a two-dimensional separation membrane using dielectric spectroscopy according to claim 4, characterized in that: The reference membrane is a graphene oxide two-dimensional membrane, and the two-dimensional separation membrane is a cation-modified graphene oxide two-dimensional membrane or anion-modified graphene oxide two-dimensional membrane; or The reference membrane is a mica two-dimensional membrane, and the two-dimensional separation membrane is a cation-modified mica two-dimensional membrane or anion-modified mica two-dimensional membrane; or The reference membrane is a COF two-dimensional membrane, and the two-dimensional separation membrane is a cation-modified COF two-dimensional membrane or anion-modified COF two-dimensional membrane; or The reference membrane is a MOF two-dimensional membrane, and the two-dimensional separation membrane is a cation-modified MOF two-dimensional membrane or anion-modified MOF two-dimensional membrane.
6. The method for predicting the confined mass transfer efficiency of a two-dimensional separation membrane using dielectric spectroscopy according to claim 5, characterized in that: When the reference membrane is a graphene oxide two-dimensional membrane, and the two-dimensional separation membrane is a cation-modified graphene oxide two-dimensional membrane, the cation-modified graphene oxide two-dimensional membrane includes Al 3+ Modified graphene oxide two-dimensional film, Mn 2+ Modified graphene oxide two-dimensional film, La 3+ Modified graphene oxide two-dimensional film or Ba 2+ One or more of modified graphene oxide two-dimensional films.
7. The method for predicting the confined mass transfer efficiency of a two-dimensional separation membrane using dielectric spectroscopy according to claim 1, characterized in that: The reference membrane or the two-dimensional separation membrane is independently selected from a graphene oxide two-dimensional membrane and a vermiculite two-dimensional membrane.
8. The method for predicting the confined mass transfer efficiency of a two-dimensional separation membrane using dielectric spectroscopy according to claim 1, characterized in that: The water is pure water or water in an aqueous system.
9. The method for predicting the confined mass transfer efficiency of a two-dimensional separation membrane using dielectric spectroscopy according to claim 8, characterized in that: The aqueous system is an alcohol-water system.
10. The method for predicting the confined mass transfer efficiency of a two-dimensional separation membrane by using dielectric spectroscopy according to any one of claims 1 to 9, characterized in that: The applicable temperature is 0-35℃.
Citation Information
Patent Citations
Method and device for judging selectivity of gas separation membrane by adopting dielectric spectrum
CN119915871A
Ion exchange membrane low in revere diffusion property and manufacturing method therefor
JP2017225962A
Method for producing porous polymer membrane and polymer composite membrane
JP2562973B2
Dielectric spectroscopy assays for screening of ion channel ligands
US20100259286A1
Classification of epigenetic biomarkers and / or DNA conformational superstructures via use of atomically thin nanopores
US20200333290A1